The Role and Position of Fatwa in Malaysian Court - Farhanin, Abdullah Asuhaimi; Nur Amani, Pauzai; Maheran, Makhtar; Khairun-Nisaa, Asari (2017)
Fatwa institution in Malaysia has been regarded as an important institution in dealing with any matters on Islamic Law, whereby its primary function is to give ruling on any issues, advice or opinion on any particular matters, or enforcement of any Islamic laws related to it. The Administration of Islamic Law Enactments in Federal Territories and other states in Malaysia have provided for the establishment of fatwa institutions in order to issue binding fatwa and regulate Islamic verdicts in states in Malaysia. Once fatwa is gazetted by the Fatwa Committee, it becomes binding on all Muslim residents of a particular state. However, the issue arose as to whether the fatwa given is also binding on the courts in making their decisions. In reaction to the above, this paper attempts to examine the practice of judges in dealing with Fatwa issued by Fatwa Committee or Mufti in its state on any particular issue as requested.